2013
DOI: 10.1111/eva.12042
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic connectivity and environmental correlates of genetic structuring in Atlantic herring in the Baltic Sea

Abstract: Marine fish often show little genetic structuring in neutral marker genes, and Atlantic herring (Clupea harengus) in the Baltic Sea are no exception; historically, very low levels of population differentiation (F ST % 0.002) have been found, despite a high degree of interpopulation environmental heterogeneity in salinity and temperature. Recent exome sequencing and SNP studies have however shown that many loci are under selection in this system. Here, we combined population genetic analyses of a large number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 80 publications
7
95
1
Order By: Relevance
“…For example, the free-floating larval stage in Atlantic herring and a later pelagic life stage mediate potential for long distance dispersal and is a likely explanation for the lack of genetic structuring for herring within the Baltic Sea shown here, as well as in previous studies using neutral genetic markers Jørgensen et al 2005). Genetic divergence among herring populations has indeed been shown to be affected more by ocean currents than geographic distance (Teacher et al 2013). Ocean currents are more likely to affect species with freefloating life stages, such as herring, or bladderwrack, for which dispersal of eggs are limited, but detached adults have the potential for dispersal by means of rafting (Tatarenkov et al 2007).…”
Section: Potential Causes Of Variability Patternssupporting
confidence: 59%
See 3 more Smart Citations
“…For example, the free-floating larval stage in Atlantic herring and a later pelagic life stage mediate potential for long distance dispersal and is a likely explanation for the lack of genetic structuring for herring within the Baltic Sea shown here, as well as in previous studies using neutral genetic markers Jørgensen et al 2005). Genetic divergence among herring populations has indeed been shown to be affected more by ocean currents than geographic distance (Teacher et al 2013). Ocean currents are more likely to affect species with freefloating life stages, such as herring, or bladderwrack, for which dispersal of eggs are limited, but detached adults have the potential for dispersal by means of rafting (Tatarenkov et al 2007).…”
Section: Potential Causes Of Variability Patternssupporting
confidence: 59%
“…The observed pattern of isolation by distance found in whitefish and pike in the present study as well as previous studies (Laikre et al 2005b;Olsson et al 2012a) is consistent with such limited dispersal and suggests that migration predominantly takes place between geographically proximate populations. It should be noted that recent studies have detected isolation by distance also in herring (Teacher et al 2013) and three-spined and nine-spined stickleback (DeFaveri et al 2012). Those studies included larger sample sizes and/or more genetic markers than examined here, however, and may thus have been characterized by higher statistical power for detection of isolation by distance.…”
Section: Potential Causes Of Variability Patternsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, coastal currents may create barriers to dispersal (Cowen et al 2006). Recent studies that combined genetics and oceanography have suggested that marine fish populations are not as open as expected (Palumbi & Warner 2003, Teacher et al 2013. Even at spatial scales of a few kilometres, meta-populations with limited gene flow can emerge in the marine environment (e.g.…”
Section: Introductionmentioning
confidence: 99%